Hydrothermal Aging of an Epoxy Resin Filled with Carbon Nanofillers - Glaskova-Kuzmina, Tatjana; Aniskevich, Andrey; Papanicolaou, George; Portan, Diana; Zotti, Aldobenedetto; Borriello, Anna; Zarrelli, Mauro (MDPI, 2020)
The effects of temperature and moisture on flexural and thermomechanical properties of neat and filled epoxy with both multiwall carbon nanotubes (CNT), carbon nanofibers (CNF), and their hybrid components were investigated. Two regimes of environmental aging were applied: Water absorption at 70 °C until equilibrium moisture content and thermal heating at 70 °C for the same time period. Three-point bending and dynamic mechanical tests were carried out for all samples before and after conditioning. The property prediction model (PPM) was successfully applied for the prediction of the modulus of elasticity in bending of manufactured specimens subjected to both water absorption and thermal aging. It was experimentally confirmed that, due to addition of carbon nanofillers to the epoxy resin, the sorption, flexural, and thermomechanical characteristics were slightly improved compared to the neat system. Considering experimental and theoretical results, most of the epoxy composites filled with hybrid carbon nanofiller revealed the lowest effect of temperature and moisture on material properties, along with the lowest sorption characteristics.
Keywords: epoxy resin; carbon nanotubes; carbon nanofibres; environmental degradation; flexural properties; modelling; property prediction model